Experimental Impacts of the "Quality Preschool for Ghana" Interventions on Teacher Professional Well-being, Classroom Quality, and Children's School Readiness. Issue 1 (2nd January 2019) - Wolf, Sharon; Aber, J. Lawrence; Behrman, Jere R.; Tsinigo, Edward
Abstract: We assessed the impacts of a teacher professional development program for public and private kindergartens in the Greater Accra Region of Ghana. We examined impacts on teacher professional well-being, classroom quality, and children's readiness during one school year. This cluster-randomized trial included 240 schools (teachers N  = 444; children N  = 3, 345, Mag e  = 5.2) randomly assigned to one of three conditions: teacher training (TT), teacher training plus parental-awareness meetings (TTPA), and controls. The programs incorporated workshops and in-classroom coaching for teachers and video-based discussion groups for parents. Moderate impacts were found on some dimensions of professional well-being (reduced burnout in the TT and TTPA conditions, reduced turnover in the TT condition), classroom quality (increased emotional support/behavior management in the TT and TTPA conditions, support for student expression in the TT condition), and small impacts on multiple domains of children's school readiness (in the TT condition). The parental-awareness meetings had counteracting effects on child school readiness outcomes. Implications for policy and practice are discussed for Ghana and for early childhood education in low- and middle-income countries.